Interactions between cardiology and oncology drugs in precision cardio-oncology. Issue 11 (11th June 2021) - Kamaraju, Sailaja; Mohan, Meera; Zaharova, Svetlana; Wallace, Brianna; McGraw, Joseph; Lokken, James; Tierney, John; Weil, Elizabeth; Fatunde, Olubadewa; Brown, Sherry-Ann
Abstract: Recent advances in treatment have transformed the management of cancer. Despite these advances, cardiovascular disease remains a leading cause of death in cancer survivors. Cardio-oncology has recently evolved as a subspecialty to prevent, diagnose, and manage cardiovascular side effects of antineoplastic therapy. An emphasis on optimal management of comorbidities and close attention to drug interactions are important in cardio-oncologic care. With interdisciplinary collaboration among oncologists, cardiologists, and pharmacists, there is potential to prevent and reduce drug-related toxicities of treatments. The cytochrome P450 (CYP450) family of enzymes and the P-glycoprotein (P-g) transporter play a crucial role in drug metabolism and drug resistance. Here we discuss the role of CYP450 and P-g in drug interactions in the field of cardio-oncology, provide an overview of the cardiotoxicity of a spectrum of cancer agents, highlight the role of precision medicine, and encourage a multidisciplinary treatment approach for patients with cancer.